Arylsulfatase A (ASA) in Parkinson’s Disease: From Pathogenesis to Biomarker Potential - Efthalia Angelopoulou; Yam Nath Paudel; Chiara Villa; Christina Piperi (Brain Sciences, 2020)
Parkinson’s disease (PD), the second most common neurodegenerative disorder after Alzheimer’s disease, is a clinically heterogeneous disorder, with obscure etiology and no disease-modifying therapy to date. Currently, there is no available biomarker for PD endophenotypes or disease progression. Accumulating evidence suggests that mutations in genes related to lysosomal function or lysosomal storage disorders may affect the risk of PD development, such as GBA1 gene mutations. In this context, recent studies have revealed the emerging role of arylsulfatase A (ASA), a lysosomal hydrolase encoded by the ARSA gene causing metachromatic leukodystrophy (MLD) in PD pathogenesis. In particular, altered ASA levels have been detected during disease progression, and reduced enzymatic activity of ASA has been associated with an atypical PD clinical phenotype, including early cognitive impairment and essential-like tremor. Clinical evidence further reveals that specific ARSA gene variants may act as genetic modifiers in PD. Recent in vitro and in vivo studies indicate that ASA may function as a molecular chaperone interacting with α-synuclein (SNCA) in the cytoplasm, preventing its aggregation, secretion and cell-to-cell propagation. In this review, we summarize the results of recent preclinical and clinical studies on the role of ASA in PD, aiming to shed more light on the potential implication of ASA in PD pathogenesis and highlight its biomarker potential.